2020
DOI: 10.1021/acs.jpcc.0c09157
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Techniques Can Distinguish the Photophysical Processes Governing Metal-Enhanced Fluorescence

Abstract: Plasmonic metal nanoparticles can impact the behavior of organic molecules in a number of ways, including enhancing or quenching fluorescence. Only through a comprehensive understanding of the fundamental photophysical processes regulating nanomolecular interactions can these effects be controlled and exploited to the fullest extent possible. Metal-enhanced fluorescence (MEF) is governed by two underlying processes, increased rate of fluorophore excitation, and increased fluorophore emission, the balance betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Nevertheless, while it is true that the scattering component of the extinction spectrum of AgNP tends to be greater for larger nanostructures of the same shape, it is the overlap between the emission spectrum of the dye and the nanoparticle scattering that is essential for MEF. In our case, the synchronous scattering (λEx = λEm) spectrum of AgNP (Dragan et al, 2013;Hodgson et al, 2020;Knoblauch et al, 2020) shows that the scattering component of the AgNP extinction well overlaps with the emission of BODIPY (Fig. S1, Supplementary Information).…”
Section: Agnp Enhances Bodipy Fluorescence In Vitromentioning
confidence: 57%
See 4 more Smart Citations
“…Nevertheless, while it is true that the scattering component of the extinction spectrum of AgNP tends to be greater for larger nanostructures of the same shape, it is the overlap between the emission spectrum of the dye and the nanoparticle scattering that is essential for MEF. In our case, the synchronous scattering (λEx = λEm) spectrum of AgNP (Dragan et al, 2013;Hodgson et al, 2020;Knoblauch et al, 2020) shows that the scattering component of the AgNP extinction well overlaps with the emission of BODIPY (Fig. S1, Supplementary Information).…”
Section: Agnp Enhances Bodipy Fluorescence In Vitromentioning
confidence: 57%
“…1B, green traces). Previously, we demonstrated that the fluorescence of green-emitting probes based on the BODIPY platform can experience MEF by large triangular silver nanoplates (∼ 80 nm), for which the surface plasmon band is centred at 660 nm (Dogantzis et al, 2020; Golian et al, 2021; Hodgson et al, 2020). Indeed, large, non-spherical nanoparticles are known to exhibit increased scattering (Knoblauch et al, 2020; Lakowicz, 2005; Lakowicz et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations